J.M. Coetzee : South Africa and the politics of writing - Attwell, David (Berkeley : University of California Press, 1993)
David Attwell defends the literary and political integrity of the South African novelist J.M. Coetzee, arguing that he has absorbed the textual turn of postmodern culture while still addressing his nation's ethical crisis. As a form of "situational metafiction," Coetzee's novels are shown to reconstruct and critique some of the key discourses in the history of colonialism and apartheid from the eighteenth century to the present. While self-conscious about fiction-making, Coetzee's work takes seriously the condition of the society in which it is produced. Attwell begins by describing the intellectual and political contexts of Coetzee's fiction. He proceeds with a developmental analysis of the corpus of six novels, drawing on Coetzee's other writings in stylistics, literary criticism, translation, political journalism, and popular culture. Attwell's elegantly written analysis deals both with Coetzee's subversion of the dominant culture around him and with his ability to grasp the complexities of giving voice to the anguish of South Africa
Acknowledgments -- Introduction -- Contexts: Literary, historical, intellectual -- "The labyrinth of my history": Dusklands and the heart of the country -- Reading the signs of history: Waiting for the barbarians -- Writing in "the cauldrons of history": Life and times of Michael K and Foe -- Conclusion: Age of iron -- Notes -- Works cited -- Index.
Includes bibliographical references (pages 135-144) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Coetzee, J. M., -- 1940- -- Criticism and interpretation; Coetzee, J. M., -- 1940-; Coetzee, J. M., -- 1940-; Coetzee, J. M. -- 1940-; Coetzee, J. M., -- 1940-; Coetzee, John Maxwell, -- (1940- ...) -- Critique et interprétation.; Coetzee, John M; Politics and literature -- South Africa -- History -- 20th century; South Africa -- In literature; South Africa -- History -- 1961-1994.; Politique et littérature -- Afrique du Sud -- Histoire -- 20e siècle.; Afrique du Sud -- Histoire -- 1961-1994.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Literature; Politics and literature; South Africa; Roman; Politiek bewustzijn; Politics and literature -- South Africa -- History -- 20th century; South Africa -- History -- 1961-; South Africa -- In literature; Politique et littérature -- Afrique du Sud -- 20e siècle.; Afrique du Sud -- Dans la littérature.; 1900-1999; English fiction; South Africa; Criticism, interpretation, etc; History